Decision experiences in joint replacement surgery for patients with haemophilic arthritis: A qualitative study - YaNan Kan; YunChun Bao; Fuying Ye (BMC Medical Informatics and Decision Making)
Abstract Background Patients with end-stage haemophilic arthritis (HA) are often hesitant about joint replacement surgery, yet little is known about the decision experiences faced by these patients. The aim of this study was to better understand the experiences faced by patients with HA when making decisions about joint replacement surgery and to provide a reference for health care professionals in the development of decision-making aids. Methods Fifteen HA patients who were candidates for joint replacement surgery at a tertiary and first-class hospital in Zhejiang Province were interviewed using a semistructured in-depth interview from January to December 2023. Colaizzi's seven-step method was used to analyse the data and refine the themes. Results The decision experience for patients with HA regarding joint replacement surgery can be summarized into four themes: decision information conflict, decision support conflict, self-perceived conflict, and self-developmental conflict. Conclusion Patients with HA face numerous decision conflicts. Health care professionals should develop joint replacement surgery decision-making aids suitable for patients with HA as soon as possible to reduce the decision conflict. Trial registration The study received approval from the Ethics Committee of Zhejiang Provincial Hospital of Traditional Chinese Medicine, China (registration date: September 22, 2023; registration number: 2023-KLS-294–01).